2016
DOI: 10.1016/j.ijsu.2016.02.064
|View full text |Cite
|
Sign up to set email alerts
|

Pancreaticoduodenectomy for adenocarcinoma of the pancreatic head is justified in elderly patients: A Retrospective Cohort Study

Abstract: Major pancreatic surgery for ductal adenocarcinoma of the pancreatic head is justified in elderly patients. With careful patients' selection and prudent perioperative management, elderly patients will have a similar long term outcome despite the higher rate of postoperative morbidity based on non-surgical complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 20 publications
3
34
0
3
Order By: Relevance
“…According to literature data [ 20 , 31 33 ], LA is indicated in patients affected by PCC up to 8 cm, incidentalomas up to 6 cm and metastases <6 cm. Thanks to the use of ultrasound or radiofrequency dissection, we also demonstrated that minimal invasive approach can be safely performed by experienced surgeons also in the treatment of benign tumors larger than 6 cm and in case of metastases, extending the previous surgical indications [ 5 , 6 , 34 , 35 ]. Regarding devices efficacy, in our series we did not observe significant differences between Harmonic scalpel™ (Ethicon Endo Surgery INC - Johnson & Johnson, NJ, USA) and LigaSure ™ vessel sealing system (Tyco, Boulder CO, USA), nevertheless we are more experienced with LigaSure ™.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…According to literature data [ 20 , 31 33 ], LA is indicated in patients affected by PCC up to 8 cm, incidentalomas up to 6 cm and metastases <6 cm. Thanks to the use of ultrasound or radiofrequency dissection, we also demonstrated that minimal invasive approach can be safely performed by experienced surgeons also in the treatment of benign tumors larger than 6 cm and in case of metastases, extending the previous surgical indications [ 5 , 6 , 34 , 35 ]. Regarding devices efficacy, in our series we did not observe significant differences between Harmonic scalpel™ (Ethicon Endo Surgery INC - Johnson & Johnson, NJ, USA) and LigaSure ™ vessel sealing system (Tyco, Boulder CO, USA), nevertheless we are more experienced with LigaSure ™.…”
Section: Discussionsupporting
confidence: 53%
“…Also robotic adrenalectomy and posterior retroperitoneal adrenalectomy (PRA) [ 4 ] represent excellent minimal invasive options, especially for benign and medium sized (<6 cm) tumors. Low morbidity rate, short hospitalization, improved cosmesis and a rapid recovery in addition to increasing patients satisfaction and comfort are the main well known advantages [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…From an international multicenter study with HIPEC following distal pancreatectomy and cytoreductive surgery, the method appears to be reasonable with minor toxicity [36]. Advances in surgery, anaesthesia, and perioperative care have resulted in significant decrease of morbidity and hospital mortality especially in high-volume centres even in elderly patients [37][38][39]. Although it is obvious that all patients underwent treatment in a small-volume centre, the hospital morbidity and mortality are acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…Однако существуют публикации, в которых оценены результаты лечения пациентов старше 80 [22] или 90 [5] лет. Так, в ряде работ [22][23][24][25][26][27] не выявлено различий летальности в разных возрастных группах. В других сериях [5,[28][29][30][31][32], наоборот, данная зависимость продемонстрирована.…”
Section: Discussionunclassified